PEDAGOGICAL POTENTIAL OF YOUTH FORUMS - V. Kayvanov (Вестник Северо-Кавказского федерального университета)
The article is devoted to the consideration of youth forums as a relatively new form and effective tool of training, education, transfer of experience to the younger generation, disclosure of potential, self-realization of youth in modern conditions. The article attempts to analyze the uniqueness of youth forums through pedagogical potential, which is a factor in the development of spirituality, morality, the conscious development and improvement ofthe personal and professional qualities ofa young person. The pedagogical potential of youth forums is considered as a holistic education with a pronounced predictive orientation, which creates an opportunity to transfer the accumulated experience, improve and implement it by the subjects of forum activities.